Pengaruh Kualititas Pelayanan dan Kepuasan terhadap Loyalitas Pelanggan dengan Inovasi Produk sebagai Variabel Intervening pada Aciak Mart - Chintya Ones Charli; Syifa Syai Ramadhani; Arya Garin Nugraha; Rini Desriyanti; Ainil Husna Chan (JURNAL RISET MANAJEMEN (JURMA), 2025)
The aim of this research is to analyze the influence of service quality and satisfaction on customer loyalty with product innovation as an intervening variable with a sample of 50 at Aciak Mart, Padang City, West Sumatra. This type of research is explanatory research. The method used is data collection using a questionnaire. SmartPls analysis method.